2013
DOI: 10.1186/1471-230x-13-89
|View full text |Cite
|
Sign up to set email alerts
|

A large nationwide population-based case–control study of the association between intussusception and later celiac disease

Abstract: BackgroundCase reports and case series studies suggest a positive association between intussusception and celiac disease (CD).MethodsWe contacted Sweden’s 28 pathology departments and obtained data on 29,096 patients with biopsy-verified CD (equal to Marsh stage 3) through biopsy reports. Patients with CD were matched for age, sex, calendar period and county of residence with up to five reference individuals from the general population (n = 144,522). Cases of intussusception were identified from nationwide inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
12
0
3
Order By: Relevance
“…11 Despite previously reported intussusception associated with CD, Ludvigsson JF et al, found no such association, but a modest increased risk of intussusception after diagnosis of CD. 14 In one prospective study, where all 150 serology-positive and biopsy-proven CD children with a median age of 72 months were screened irrespective of symptoms, intussusception was present in 25% with 95% involving small bowel. All but one had asymptomatic intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…11 Despite previously reported intussusception associated with CD, Ludvigsson JF et al, found no such association, but a modest increased risk of intussusception after diagnosis of CD. 14 In one prospective study, where all 150 serology-positive and biopsy-proven CD children with a median age of 72 months were screened irrespective of symptoms, intussusception was present in 25% with 95% involving small bowel. All but one had asymptomatic intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] It is the most common cause of intestinal obstruction at pediatric ages and needs prompt intervention, which may be surgical or nonsurgical.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nonetheless, using a prospective cohort approach, a post-hoc analysis found that 12 out of 29,060 individuals with celiac disease were given a diagnosis of intussusception after the onset of celiac disease, with a modest but significant increase risk of intussusception after celiac disease had been diagnosed (odds ratio, OR = 1.95; 95% confidence interval, CI = 1.01-3.77; P = 0.046). In that study, patients with celiac disease without symptoms were not serially investigated with abdominal imaging, which may have reduced the absolute numbers of patients with subclinical intussusception who did not seek acute care and were unaccounted for.…”
mentioning
confidence: 99%
“…Typical symptoms are abdominal pain, nausea, lethargy, vomiting and sometimes bleeding from the rectum ("red currant jelly") [8]. However, the most common presentation is the triad of abdominal mass, tenderness, and hemoglobin-positive stools.…”
Section: Discussionmentioning
confidence: 99%